2006
DOI: 10.1002/jsfa.2478
|View full text |Cite
|
Sign up to set email alerts
|

Total and ileal digestible tryptophan contents of feedstuffs for broiler chickens

Abstract: Reliable values of total and digestible tryptophan in components of feed formulation matrices are needed because tryptophan is often the third limiting amino acid in practical poultry diets. However, tryptophan is oxidatively destroyed during acid hydrolysis in routine amino acid analysis and its determination requires a separate analytical procedure. The variability in contents and apparent ileal digestibility for 6-week-old broiler chickens of tryptophan in 74 samples representing 24 feedstuffs are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In monogastric animals, the main effects of tannins are related to their protein-binding capacity and reduction in protein, starch, and energy digestibility [ 76 , 77 ]. According to [ 10 , 78 ], dry matter intake, bodyweight, feed efficiency and nutrient digestibility were reduced when chickens were fed diets with tannins, whilst Ebrahim et al [ 71 ] reported a decrease in body weight gain and feed intake. However, [ 72 , 75 ] reported no effects on growth performance and on egg weight, cell thickness or yolk color of layers.…”
Section: Influence Of Tannins On the Productivity Of Monogastric Amentioning
confidence: 99%
“…In monogastric animals, the main effects of tannins are related to their protein-binding capacity and reduction in protein, starch, and energy digestibility [ 76 , 77 ]. According to [ 10 , 78 ], dry matter intake, bodyweight, feed efficiency and nutrient digestibility were reduced when chickens were fed diets with tannins, whilst Ebrahim et al [ 71 ] reported a decrease in body weight gain and feed intake. However, [ 72 , 75 ] reported no effects on growth performance and on egg weight, cell thickness or yolk color of layers.…”
Section: Influence Of Tannins On the Productivity Of Monogastric Amentioning
confidence: 99%
“…Chickpeas is a good source of lysine, but deficient in methionine and cysteine. A tryptophan content of 1.8 g/kg (as received basis) was reported in chickpeas [140]. As suggested by Chiaiese et al [147], the use of transgenic techniques would help overcome the deficiency of these limited AAs.…”
Section: Chickpeasmentioning
confidence: 92%
“…Although diets were supplemented with vitamin premix, possible additional vitamin B coming from RD might have been favourable for birds fed the test diets. Blood meal has a high digestibility coefficient of tryptophan, the third limiting amino acid in broilers (Ravindran et al 2006). Tryptophan stimulates growth and protein accretion through regulation of metabolic pathways (Wu 2013;Qaid and Al-Garadi 2021).…”
Section: Growth Performancementioning
confidence: 99%